Observations of juvenile sandbar sharks Carcharhinus plumbeus (Nardo, 1827) around the Bojana River delta (Southern Adriatic Sea) - ĆETKOVIĆ, ILIJA; JAMBURA, PATRICK L.; PEŠIĆ, ANA; IKICA, ZDRAVKO; JOKSIMOVIĆ, ALEKSANDAR (Mediterranean Marine Science, 2022)
The sandbar shark (Carcharhinus plumbeus) is considered rare in the Adriatic Sea and the majority of records originate from the northern Adriatic, where a nursery area for this species close to the Po delta system has been repeatedly proposed. This study provides 5 new records and analyses the previously published records of sandbar sharks recorded around the delta of the River Bojana (in Montenegro, in the south-eastern Adriatic). The River Bojana located on the border between Montenegro and Albania, is the second largest river flowing into the Adriatic Sea, where it forms a highly productive ecosystem already known as a local hotspot for smooth-hound sharks (Mustelus spp.). New records of sandbar sharks have emerged as a result of citizen science (a social media survey) and direct reports from fishermen. The total length of C. plumbeus juveniles ranged from approximately 800 mm to 1100 mm, and most (n=5) were caught by set gillnets. The data presented here show that juveniles are consistently present around the estuary and indicate the importance of this fragile estuarine ecosystem for sandbar sharks. Additionally, this study also provides morphometric data collected from a single individual.